An unusual case of infective endocarditis with acute limb ischemia and cardiac embolism. (2021) - Daoud, Nour; Malikayil, Kiran; Regalla, Dinesh; Alam, Mohammad
Abstract: Infective endocarditis (IE) is a persistent health issue, particularly among intravenous drug users. We discussed a case of infective endocarditis in a patient who uses IV drugs, which had some unusual features such as unusual presentation, polymicrobial infection, left-sided valve involvement, coronary embolism, and an uncommon pathogen for IE.